HPV strain prevalence and HPV-related biomarker expression in vulvar carcinoma at Tygerberg academic hospital. - Petersen, Nadine Samantha (Stellenbosch : Stellenbosch University, 2019)
Thesis (MMed)--Stellenbosch University, 2019.